DISKUSI KEBANGSAAN DAN HAK PILIH PARA PEMILIH PEMULA DI KELURAHAN KEMLAYAN KECAMATAN SERENGAN KOTA SURAKARTA - MUKHLISAH, IFFAH; PRAPTININGSIH, PRAPTININGSIH; APRILIYANI, ERLY; SULISTYORINI, LENI; AULIYA, NISA’ (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to provide a deeper understanding of national values ??to first-time voters, provide political knowledge, especially about exercising voting rights for first-time voters in the 2024 election, and increase the active participation of first-time voters to make the election a success. In the field, there are still many young people who do not understand the importance of their right to vote in building and determining the direction of progress of this nation and state, apart from that, many beginner voters are still confused about the stages in exercising their right to vote, and beginner voters have a low understanding of the right to vote to cast their vote. and upholding national values ??and patriotism. Service activities are carried out by means of socialization activities in the form of national seminars followed by interactive dialogue in a series of activities. The resource person for the activity came from the Bawaslu city of Surakarta who were very professional and trained. The activity was organized by the PKN-T Group 7 IIM Surakarta Community Service team and the Kemlayan Serengan Surakarta sub-district government. The seminar activities were attended by approximately 28 young people aged 17-22 years. This activity makes new voters understand more about the values ??of diversity, love for the country and nation, increases the enthusiasm of new voters who will exercise their right to vote, and make the election a success. The young people who are members of the group of beginner voters hope that discussion and dialogue activities about nationality need to be continued into a program that can be packaged in more relaxed, familiar activities, even if on a small scale. New voters have high hopes for assistance from the Kemlayan sub-district government for youth programs to continue to uphold national values. From seminar activities and national discussions, young people are more open and more enthusiastic in exploring nikai kengsaan not only in theory, but also in practice in everyday life. ABSTRAK Pengabdian ini bertujuan untuk memberikan pemahaman yang lebih mendalam terhadap nilai-nilai kebangsaan kepada para pemilih pemula, memberikan pengetahuan politik terutama tentang menggunakan hak pilih para pemilih pemula pada pemilu tahun 2024, dan meningkatkan partisipasi aktif para pemilih pemula untuk mensukseskan pemilu. Di lapangan masih banyak para pemuda yang belum memahami pentingnya hak pilih mereka dalam membangun dan menentukan arah kemajuan bangsa dan negara ini, selain itu banyak pemilih pemula masih bingung tentang tahapan-tahapan dalam memakai hak pilih mereka, rendahnya pemahaman pemilih pemula tentang hak pilih menyalurkan suara dan menjungnjung tinggi nilai-nilai kebangsaan dan rasa cinta tanah air. Kegiatan engabdian dilakukan dengan cara kegiatan sosialisasi dalam bentuk seminar kebangsaan yang dilanjutkan dengan dialog interaktif dalam satu rangkaian kegiatan. Nara sumber kegiatan berasal dari bawaslu kota Surakarta yang sangat profesional dan telatih. Kegiatan diorganisir tim Pengabian PKN-T kelompok 7 IIM Surakarta dan pemerintah kelurahan Kemlayan Serengan Surakarta. Kegiatan seminar diikuti oleh para pemuda yang berusia 17-22 tahun berjumlah kurang lebih 28 pemuda-pemudi. Kegiatan tersebut menjadikan para pemilih pemula lebih memahami tentang nilai-nilai kebinekaan, cinta tanah air dan bangsa, meningkatkan antusias pemilih pemula yang akan menyalurkan hak pilih, dan mensukseskan pemilu. Para pemuda yang tergabung dalam kelompok pemilih pemula berharap kegiatan diskusi dan dialog tentang kebangsaan perlu dilanjutkan menjadi sebuah program yang bisa dikemas dalam kegiatan yang lebih santai, akrap walaupun dalam skala kecil. Besar harapan para pemilih pemula adanya pendampingan dari pemerintah kelurahan Kemlayan terhadap program-program para pemuda untuk tetap menjunjung nilai-nilai kebangsaan. Dari kegiatan seminar dan diskusi kebangsaan para pemuda lebih terbuka dan lebih antusias dalam mendalami nikai kengsaan tidak hanya secara teori, tetapi juga praktik di kehidupan sehar-hari.